Integrating approaches to analyzing English e-mail correspondence in an import-export business - Tangpijaikul, Montri (วารสารภาษาปริทัศน์, 2020)
It has been suggested that skills in email communication be incorporated into pedagogy, but one problem in achieving this is the paucity of studies of business emails. This research reports findings from a corpusbased analysis of business email negotiations, conducted as a case study. The study explores turn-taking patterns, speech acts and interactional metadiscourse markers in a case of business negotiation via emails to observe the dynamics of business interaction and buyer-seller relationships which vary across time and stages throughout the course of e-negotiations. Findings reveal the one-to-one turn taking pattern at the in-business negotiation phase where important decisions are made, but when problems occur both parties cooperate as can be seen in many-to-many turn taking patterns in the final shipping phase. Representative, directive and expressive acts conveyed by the seller prevail those used by the buyer during the initial contact, but later the buyer seems to express several types of speech acts more frequently.Engagement and attitude markers are used most frequently in the middle stage of the negotiation when the business relationship is critical while selfmentions are preferred in the final shipping stage which aims at solving problems. Business English learners should be made aware of the interactional linguistic features available in the English language and be given a chance to exercise them. Ideas on teaching business interactional discourse are suggested in the discussion.